Complicity and causality - Gardner, J (Springer, 2007)
This paper considers some aspects of the morality of complicity, understood as participation in the wrongs of another. The central question is whether there is some way of participating in the wrongs of another other than by making a causal contribution to them. I suggest that there is not. In defending this view I encounter, and resist, the claim that it undermines the distinction between principals and accomplices. I argue that this distinction is embedded in the structure of rational agency.